Characteristics of Patients with Post-Traumatic Stress Disorder (PTSD) at Ibnu Sina Teaching Hospital, Makassar - Nilam Nilam; Sri Vitayani; Mayamariska Sanusi; Muhammad Alim Jaya; Nevi Sulvita Karsa (Jurnal Info Sains : Informatika dan Sains, 2025)
Background: Post Traumatic Stress Disorder (PTSD) is a trauma- and stressor-related mental disorder that can significantly impair psychological, social, and occupational functioning. Despite increasing awareness of PTSD in Indonesia, local data describing patient characteristics remain limited, particularly in teaching hospital settings. Objective: This study aimed to describe the demographic characteristics, types of traumatic exposure, and dominant symptom clusters of PTSD patients treated at Ibnu Sina Makassar Teaching Hospital. Methods: This descriptive cross-sectional study used medical records of PTSD patients treated at the Psychiatric Outpatient Clinic of Ibnu Sina Makassar Teaching Hospital from September 2024 to September 2025. All eligible patients were included using total sampling. Data were analyzed descriptively. Results: Most patients were aged 19–39 years (60.0%) and were female (62.0%). The majority had a senior high school education (60.0%) and were students (46.0%). Interpersonal conflict was the most common traumatic exposure (32.0%), followed by physical violence (26.0%) and occupational trauma (18.0%). Intrusive symptoms were the most frequently reported PTSD symptom cluster (38.0%), followed by negative alterations in mood and cognition (26%) and arousal and reactivity symptoms (22%). Conclusion: PTSD at Ibnu Sina Makassar Teaching Hospital predominantly affected young adults, females, and students, with interpersonal trauma as the leading precipitating factor. These findings highlight the need for targeted, trauma-focused mental health interventions and provide valuable local epidemiological data to support evidence-based PTSD management and service planning.